Gamification as a Digital Marketing Strategy: Impact on Customer Value, Purchase Decision, and Repurchase Intention - Siti Alhamra Salqaura; Nasib Nasib; Siti Sabrina Salqaura (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2026)
Businesses increasingly use gamification to create interactive digital experiences that strengthen customer engagement and loyalty. This study examines the effects of gamification on customer value, purchase decision, and repurchase intention among Shopee users in Medan City, Indonesia. A quantitative survey was administered to 267 respondents who had used Shopee and made at least two purchases, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that gamification significantly influences purchase decision (b = 0.938, p 0.001) and repurchase intention (b = 0.934, p 0.001). Customer value also significantly affects purchase decision (b = 0.551, p 0.001) and repurchase intention (b = 0.501, p 0.001). Mediation testing indicates significant indirect effects of gamification on purchase decision through customer value (b = 0.515, p 0.001), gamification on repurchase intention through purchase decision (b = 0.192, p = 0.003), and customer value on repurchase intention through purchase decision (b = 0.250, p = 0.002). However, customer value does not significantly mediate the effect of gamification on repurchase intention (b = 0.234, p = 0.059). These findings suggest that gamification strengthens digital consumer behavior when it enhances perceived value and facilitates purchase decisions.